Improving Contextual Abilities through Problem-Based Learning and Teaching at the Right Level - Ariyanti, Gregoria; Amalia, Nabilla Dihni; Purwaningsih, Purwaningsih; Jr, Rosalio G. Artes (Studies in Learning and Teaching, 2025)
This study aims to analyze the process and results of improving students' mathematical abilities in solving contextual problems through the implementation of the Problem-Based Learning (PBL) model and the Teaching at the Right Level (TaRL) approach. The PBL model is designed to develop problem-solving and critical thinking skills through problems relevant to the real world. The TaRL approach is integrated to accommodate the heterogeneity of students' levels of understanding through identifying individual needs and providing guidance. The Kemmis and McTaggart Classroom Action Research (CAR) model was carried out for two cycles. The subjects of the study were 32 students in the second grade of senior high school in Surabaya. Data collection techniques included contextual problem-solving ability tests (descriptions) and participatory observations using teacher and student observation sheets. Quantitative data were analyzed descriptively to calculate the average class score and percentage of learning completion. Minimum competency achievement is 75. Qualitative data were analyzed to describe the quality of the learning process. The results showed a significant increase. In cycle 1, the average class score reached 85.47 (good category) with a completion of 84.38%. The improvement continued in cycle 2, where the average value increased to 89.12 (Very Good category) and completion reached 93.75%. The novelty of this research lies in integrating the Problem-Based Learning (PBL) model with the Teaching at the Right Level (TaRL) approach, a combination rarely used to simultaneously improve students' problem-solving abilities and address differences in learning levels within the same class.